An empirical investigation of a weight-wage penalty due to taste-based discrimination in Australia - Charhill, Phillip (My University, 2023)
We measure the weight-weight penalty faced by employed adults in Australia by using the HILDA dataset and decompose this into justified (productivity based) and unjustified (taste-based) discrimination at both the hiring stage and after employment is atained. We find evidence that a taste-based penalty on pay is placed upon obese workers, which is larger for men and smaller for women. Our result is subject to which subsample of our penal we study.
Keywords: Health and wellbeing; Income, wealth and finances; Labour market